Perancangan Fleksibel Antena Dengan Substrat Polyethylene Terephthalate (PET) Untuk Pendeteksian Tumor Pada Payudara - Rosdiansyah, Rosdiansyah; Rahayu, Yusnita; Wahyu, Yuyu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Cancer is one of the leading causes of death worldwide. Early detection is the best solution for cancer treatment. The UWB microwave imaging technology is one of the most promising technologies in the field of medical diagnosis, because it is non-ionizing and low cost. One of the most important elements in a microwave imaging system is an antenna. Recently, the flexible electronic is used as substrate for microstrip antenna. This paper will proposed the design of flexible antenna for breast tumor detection. The proposed antena is designed using Polyethylene Terephthalate (PET) as substrate and silver as patch. The simulation result shows flexible antenna is work at 5.8 GHz frequency with -25.27 dB value of return loss, 1.115 value of VSWR, 3.37 GHz bandwidth, 58.1% GHz impedance bandwidth and 2.68 dBi Gain. By using a flexible substrate, the antenna can follow the structure of the breast and can be placed in the breast for better breast tumor detection. Keywords: Breast tumor detection, Flexible Antenna, Polyethylene Terephthalate (PET), Ultrawideband (UWB)